MELALUI PENDIDIKANAGAMAHINDU MENINGKATKANSRADHA MAHASISWADI KAMPUS IHDN DENPASAR - Seriadi, Si Luh Nyoman (Jurnal Penjaminan Mutu, 2015)
Education is one of the fundamentals for the Hindus in this modern globalisation. As the increasing negative influence due to lacking of good religious values. This study discusses problems, such as (1) what is Faculty of Dharma Acarya (FDA)?; (2) what should be done to improve the facultyâ; (3) what benefits would be there if the quality of the faculty increases? This study concluded that Hindu education should be aimed at improving the Sradhaand Bhakti of the IHDN Denpasar students, the religious skills, and the intellectualities, building the characters, strengthening the personalities, andthe loyalty to the country as well as to the Balinese own culture.